Primary, main, and major : learning the synonyms through corpus data - Supakorn Phoocharoensil, (Penerbit Universiti Kebangsaan Malaysia, 2022)
English is widely known as a language containing a number of near-synonyms, i.e. words with similar meaning, and therefore English learners are often confronted with difficulty in the use of near-synonyms in different contexts. This corpus-informed study aims to differentiate the synonyms primary, main, and major, focusing on their distribution across genres and collocation usage. The three target synonyms were selected as main and major are among the first 1,000 words in spoken and written English (Longman Dictionary of Contemporary English, 2014), while primary appears in Coxhead’s (2000) Academic Word List (AWL). The data from the Corpus of Contemporary American English (COCA) demonstrated that the three synonymous adjectives most frequently occur in academic texts, with primary being more common in newspapers and magazines. Through a collocation analysis based on frequency and MI score, concern strongly collocates with all three adjectives, while some noun collocates are frequently combined with only certain pairs of synonyms, e.g. primary/main focus, a main/major theme, and a primary/major factor. More interestingly, some noun collocates are attached to specific semantic themes, with primary being exclusively associated with health and election, main with place, food, or literature, and major with sports or business. As to the implications for ELT, teachers are encouraged to develop synonym lessons based on typical collocates derived from authentic corpus-based English, e.g. COCA.